Hypoglycemia-induced Bispectral index changes during Coronary Artery Bypass Surgery (CABG): A case report - Madadi, Firoozeh; Behnaz, Faranak; Ariannia, Hamideh; Faridi, Ako; Khorasanizadeh, Mahtab (Novelty in Biomedicine, 2024)
Background: Diagnosing hypoglycemia is a widely known challenge for anesthesiologists during the perioperative period, especially under general anesthesia, during which many signs and symptoms would be masked. On the other hand, the bispectral index, which has recently been utilized to measure the depth of anesthesia, may be influenced by other factors such as hypo and hyperglycemia. Cases Report: Herein, we have presented a case of a patient who experienced an abrupt decrease in the Bispectral index following hypoglycemia. Conclusion: Although the Bispectral index is widely used to monitor anesthesia depth, it can be utilized to continuously monitor other contributing factors such as glycemic condition, hypothermia, hypovolemia, and cerebral ischemia.